Persepsi Dan Prefrensi Pengunjung Terhadap Daya Tarik Gelangang Olahraga Purna Krida Kerobokan, Badung - Artha, Anak Agung Gede Pradnyana; Sugianthara, Anak Agung Gede; Asmiwyati, I Gusti Agung Ayu Rai (Jurnal Arsitektur Lansekap, 2023)
Visitors Perceptions and Preferences on the Attraction of the Purna Krida Kerobokan Sports Center, Badung . Sports activities and the expertise of athletes also need to be given a place as a means of training to increase public interest in sports and the expertise of the athletes' abilities to perform better is influenced by several factors. One of the influencing factors is the provision of facilities, both in terms of buildings and supporting equipment for sports activities. Purna Krida Sports Center (GOR Purna Krida). GOR Purna Krida on Jl. Raya Kerobokan No.11, North Kuta District, Badung Regency. The purpose of this research is to find out how the perception and preference of GOR Purna Krida in 3 segments, namely Beauty, Comfort, Security, visitors to the attractiveness of using perception. The method used in this study is a survey method with data collection techniques, observation, questionnaires, interviews and library studies. The results of the research average value of 8% quite beautiful, 68% beautiful, and 24% less beautiful, in terms of comfort 5% comfortable, 72% quite comfortable, and 23% less comfortable, in terms of security 52% quite safe, 35% safe and 13% less safe.